The association of the JNK scaffold protein, WDR62, with the mixed lineage kinase 3, MLK3 (MAP Kinase, 2015)
Mitogen-activated protein kinases (MAPKs) form a kinase tier module in which MAPK, MAP2K and MAP3K are held by scaffold proteins. The scaffold proteins serve as a protein platform for selective and spatial kinase activation. The precise mechanism by which the scaffold proteins function has not yet been fully explained. WD40-repeat protein 62, WDR62 is a novel scaffold protein of the c-Jun N-terminal kinase (JNK) pathway. WDR62 is a 1523 a.a. long protein with no significant sequence homology to a known gene. Previously WDR62 was shown to associate with JNK and MKK4/7 in a modular fashion. Here, we show that WDR62 is able to associate with multiple members of the MAP3K of the mixed lineage kinase family and we map WDR62-MLK3 interacting domains. We identify two separable interacting domains within WDR62 and MLK3 proteins that can cross associate. MLK3 association with WDR62 is independent of JNK and MKK4/7 domains and activities. CDC42 activation disrupts WDR62-MLK3 association independent of MLK3 kinase activity.
Keywords: c-Jun N-terminal kinase; MLK3; Scaffold; WDR62.